Monitoring and diagnostic system as a tool for increasing technical assistance for tractors - Prokopov S. P.; Soyunov A. S.; Demchuk E. V.; Golovin A. Yu.; Abdylmanova R. Kh. (E3S Web of Conferences)
The article analyses the dependence of violation of agrotechnical terms of technological operations on the technical condition of tractors and agricultural machinery. The study analysed the tractor park age of agricultural enterprises on the example of the Siberian region and revealed that the average age of tractors is more than 10 years - this affects their reliability and serviceability in busy periods of field works. Tractors of such age are not equipped with control systems, which does not allow real-time monitoring of diagnostic parameters (technical condition) of their systems and mechanisms. In order to improve the reliability and serviceability of tractors and their timely and quality maintenance, a remote monitoring and diagnostics system has been developed. The application of this system contributes to the improvement of the quality of performed maintenance works by monitoring the tractor performance indicators in real time mode and, consequently, ensuring compliance with the terms of maintenance operations. In the course of researches the board and sensors of fuel consumption, temperature of low-freezing liquid, crankshaft revolutions, positioning (coordinates) and determination of tractor speed were selected, codes of data transmission and processing from sensors to the monitoring device were obtained and their correct operation was checked. The functioning of sensors and platforms was checked. Web-application was developed and tested, wi-fi network was used as a communication method. Output of information from the device is carried out in two browser windows using the standard IP address of the boards.